Histomorphological spectrum of Leiomyoma – a one year retrospective study - Baral, Reetu Sharma; Shrestha, Oshan (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To analyze the histomorphology of leiomyoma in specimens received in Pathology. Methods: This is a retrospective descriptive study of histopathology database of histomorphologic spectrum of leiomyoma at Pathology Laboratory of Nobel Medical College Teaching Hospital, Biratnagar, Nepal from April 2020 to April 2021. Data for the leiomyoma were analyzed descriptively. Ethical approval was obtained from the Institutional review committee. Results: A total of 1705 histopathology specimens were received in one year from April 2020 to April 2021 out of which 620 (37%) were from the Department of Gynecology and Obstetrics for histopathological analysis of various specimens. Total of 106 specimens of hysterectomy and myomectomy were included. Maximum number of leiomyoma was seen in the body 48 (45%) followed by fundus 34 (32%) and one from the lateral wall of the vagina 1 (0.9%). Mean age was 42 (24-70) years. Maximum size was 35 cm and minimum was 0.5 cm in diameter. Out of the rare ones one case of STUMP, Lipoleiomyoma and Mitotically active leiomyoma each were seen. Degenerative change was in 40 cases with hyaline type as the commonest one (33%); 61% were intramural; and 12% were multiple. Presentation was lower abdominal pain and abnormal uterine bleeding in 39.6%. Conclusions: Cases of leiomyoma may present with abdominal mass, pain and bleeding but the degenerative changes and malignant transformation can't be identified without histopathological examination.